EXTRALINGUISTIC AND LINGUISTIC FACTORS OF EMERGENCE AND FORMATION OF UKRAINIAN TERMINOLOGY OF FOOD INDUSTRY - О. В. Нарушевич-Васильєва (Записки з українського мовознавства, 2017)
The article reveals the main stages of formation of Ukrainian terminology of food industry (hereinafter FI), and describes a leading trends in terminology at each of the studied historical stages. The use of comparative historical method of analysis made it possible to justify the gradual systematization of FI terminology as a historically conditioned process, in which interacts linguistic and extra-linguistic reasons. It is defined in the article that the dynamics of the formation and development of Ukrainian terminology of FI was determined primarily by the action of extra-linguistic factors: progressive changes in the development of science and technology, the development of various branches of food production in Ukraine, and the intensification of intercultural contacts. It is also defined that terms formation and terms regulations in the sphere of FI directly depends on the participation in these processes of scientists and linguists, bright personalities and their contribution to the development of the Ukrainian language of the FI. Purely linguistic factors on the formation of the branch vocabulary of the FI is analyzed in the article, among which the most important are the desire to deepen and broaden the idea of an object or phenomenon, to elaborate the concept; to eliminate the polysemy of the term; to introduce to the scientific circles the most semantically precise terminology unit.  The study of the peculiarities of the formation and functioning of the terminology of the FI gives an idea of the state of the terminological science on the field of food industries and allows us to determine the problems of its further development, among which we can name: description of the core terms of the FI and its ordering with preservation of national specificity, study of the adaptation of modern borrowed terms of FI, research of the reasons for the occurrence of terms-variants.